The possibility of using the DKS-AT1123 dosimeter for radiation monitoring of medical electron accelerators with the energy of more than 10 MeV - A. N. Barkovsky; S. A. Ogorodnikov (Радиационная гигиена)
In  the  Russian  Federation,  there  is  a  constant  increase  in  the  number  of  radiation  medical  installations  with electron accelerators. Over the past 4 years, their number has increased 2.5 times. These installations contain pulsed electron accelerators that generate pulsed bremsstrahlung radiation with a maximum energy from 6 to 21 MeV. Currently, there are no devices designed for dosimetry of the pulsed photon radiation with energy of more than 10 MeV in the state register of measuring instruments of the Russian Federation. The most widely used radiation monitoring device for pulsed electron accelerators is the DKS-AT1123 X-ray and gamma radiation dosimeter designed for dosimetry of pulsed bremsstrahlung radiation with an energy of up to 10 MeV. The purpose of this work is to evaluate the possibility of using this device for dosimetry of pulsed bremsstrahlung radiation with a maximum energy of up to 20 MeV. The authors calculated the energy spectra of bremsstrahlung radiation for a point source with a maximum energy of 20 MeV behind flat concrete screens with a thickness of 1 m, 2 m and 3 m by the Monte Carlo method using the GEANT4 calculation program. The energy dependence of the registration efficiency of the DKS-AT1123 dosimeter was extrapolated to the energy range of 10–50 MeV in the kerma-approximation without taking into account the energy transfer by secondary electrons. It was assumed that it corresponds to the energy dependence of the total mass attenuation coefficient for the absorbed energy of gamma quanta in water. Using conversion coefficients for converting the fluence of monoenergetic photons into the effective dose rate at an anterior-posterior radiation incidence on the human body, real dose rates were calculated, and using the energy dependence of the dosimeter readings, the predicted results of measuring the unit dose rate with the DKS-AT1123 dosimeter behind a concrete protection with a thickness of 1, 2 and 3 m were obtained. It is shown that the maximum expected underestimation of the measurement results will not exceed 40% and practically does not depend on the thickness of the concrete shield in the thickness range from 1 to 3 m. To account for this underestimation, it is necessary to use the value of additional measurement error due to the energy dependence of the sensitivity of this device for the photon radiation energy of more than 10 MeV, equal to 70%. This makes it possible to use the measurement results obtained using this dosimeter to adequately characterize the state of radiation safety during operation of pulsed electron accelerators with a maximum energy of up to 20 MeV. It is possible to use a correction factor to the measurement results equal to 1.63 ±0.04 to compensate for this underestimation. The proposed approach can be used to create a methodology for using this dosimeter for radiation monitoring of medical electron accelerators with the energy of up to 20 MeV, if there are correction factors for radiation protection configurations and radiation energies encountered in practice.